The characterization of bacteriocins produced by Lactobacillus plantarum strains isolated from traditional fermented foods in Indonesia and the detection of its plantaricin-encoding genes - Sogandi Sogandi; Apon Zaenal Mustopa; I Made Artika (Indonesian Journal of Biotechnology, 2019)
Lactobacillus plantarum is widely found in either anaerobic plant matter or fermented foods, and it has been recognized as producing antimicrobial bacteriocins. This study aimed to characterize the antimicrobial bacteriocins of L. plantarum and detect its genes that encode plantaricins. Samples were isolated from traditional fermented foods from Indonesia. Antimicrobial activity was evaluated using the agar diffusion assay procedure. The titration method applied the maximum amounts of lactic acid at 1054 mg/mL and hydrogen peroxide at 3.85 mg/mL. Based on the results, the supernatant of the L. plantarum strains appeared to have a broad spectrum of antimicrobial activity against pathogens, which would be active at pH 2.0–12.0 and stable temperature. In addition, almost all of the L. plantarum strains contained plantaricin-encoding genes (e.g. plnA, plnF,plnJK, and plnW), which were grouped into one cluster as indicated by phylogenetic analysis. Therefore, this study discovered clear evidence of the potential of some L. plantarum strains to act as antimicrobial agents.